Cấu trúc vốn của các ngân hàng thương mại Việt Nam: Cách tiếp cận theo phương pháp Bayes - Pham Hai , Nam; Huynh Thi Tuyet , Ngan; Nguyen Ngoc, Tan; Pham Thi Hong , Nhung; Nguyen Tran Xuan , Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The objective of the study is to find out the factors affecting the capital structure of commercial banks in Vietnam, including the group of state-controlled joint stock commercial banks and the group of private joint stock commercial banks. In this study, the author uses the debt-to-total asset ratio to represent the capital structure of Vietnamese commercial banks. The study applied Bayesian regression method via Gibbs sampling algorithm with data set including 3 state-controlled joint stock commercial banks and 27 private joint stock commercial banks in Vietnam over the period 2007–2018. The research results show that the factors that have a positive impact on the capital structure of state-controlled joint-stock commercial banks include asset size, asset growth rate, bank age, inflation, and GDP growth. The factors that have the opposite effect are profitability and liquid assets. For the group of private joint stock commercial banks, the factors that have a positive impact are asset size, asset growth rate, liquid assets, GDP growth. The factors that have the opposite effect are profitability, bank age, and inflation.